2019
DOI: 10.3390/ijerph16050895
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Women’s Autonomy and Experience of Intimate Partner Violence as a Predictor of Maternal Healthcare Service Utilization in Nepal

Abstract: This study aims to identify the relationship of women’s autonomy and intimate partner violence (IPV) with maternal healthcare service utilization among married women of reproductive age in Nepal. This study used data from the 2016 Nepal Demographic and Health Survey (NDHS), which is a nationally representative sample survey. The association between outcome variables with selected factors were examined by using the Chi-square test (χ2), followed by multiple logistic regression. The sample was adjusted for multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 43 publications
5
35
1
Order By: Relevance
“…This consistency could be supported by a male-dominated marital power structure has been documented to be highly related with marital con ict and husband-to-wife violence (48). Women's decision-making autonomy is not only reduced the risk IPV but also increased the utilization of maternal service (31,49).…”
Section: Discussionmentioning
confidence: 96%
“…This consistency could be supported by a male-dominated marital power structure has been documented to be highly related with marital con ict and husband-to-wife violence (48). Women's decision-making autonomy is not only reduced the risk IPV but also increased the utilization of maternal service (31,49).…”
Section: Discussionmentioning
confidence: 96%
“…However, there is evidence that partner controlling behaviour is a reflection of power dynamics in an intimate relationship and indicates imminent risk of other forms of abuse [27,39]. Studies have also revealed that partners' control influences women's decision-making power [27], health service access and utilization [27,40], and fertility control [15,41,42]. Therefore, we have adopted the World Health Organization (WHO) definition of IPV (1 p89) and included partner control as a form of IPV in our analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to women's working status, those who are working are more likely to be educated, involve in household decision making and get access to reproductive health services than those who are not. The ANC visits help young women have better understanding of risk in regard to the complication of pregnancy and childbirth and enable them to make a decision regarding the use of SBAs [41].…”
Section: Discussionmentioning
confidence: 99%